DC magnetic bias suppression strategy for series transformers in dynamic voltage restorers. Issue 4 (May 2019) - Wang, Ziang; Meng, Runquan; Sun, Zhi
Abstract: In actual engineering, the dynamic voltage restorer is mainly used to protect the load from the voltage drop of the grid, and is inserted between the grid and the load through the series transformer. The dynamic voltage restorer (DVR) can easily cause DC bias and generate magnetizing inrush current at the beginning of compensation voltage drop. This is also a common problem in DVR engineering applications. The usual way to solve this problem is to design the transformer core to twice the rating, but this will greatly increase the size and cost of the transformer. In order to ensure the safe, reliable and stable operation of the DVR and reduce the cost and volume of the transformer, it is necessary to suppress DC bias of the transformer. Based on the principle analysis of the DC bias generation in series transformers, a DC bias suppression strategy was proposed to control the amplitude of the first half of the output voltage of the DVR. The DVR system model was built in Simplorer, Matlab and Maxwell for co-simulation, and the effects before and after the DC bias suppression strategy were compared.